Integration of Islamic Economics in the Revitalization of National Food Barns: A Literature Review - Hidayat, Surahman; Najamudin, Najamudin (Sahabat Publikasi, 2025)
Global food security faces serious challenges due to conflicts between countries and climate change, which increase food insecurity, especially in developing countries such as Indonesia. Various programs, such as the national food barn and the revitalization of community food barns, have been initiated by the government to maintain food security. However, the integration of Islamic economics in this policy has not been utilized optimally. This study analyzes the application of Islamic economics in the revitalization of community food barns through a philosophical, contextual, and practical approach, using literature studies. The results show that the community's food barn has a strong theological foundation from the Qur'an and Hadith, and can be developed more effectively through Islamic economic instruments, such as zakat, infaq, and sharia financing. The research recommendations include the application of Islamic economic integration in the management of community food barns and the development of an operational framework to support its implementation